Inovasi Kelembagaan Pendidikan Islam Perspektif KH. Ahmad Dahlan dan Relevansinya di Era Modern - Al Fithri, Qurrota A'yun; Maula, Aris Rohmatul; Azizah, Nur Amalina Wafi’; Diana, Alfi Elma (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
Islamic educational institutions in Indonesia continue to develop as education distributors. That proves that Islamic education is continuously developing and educating the nation's children. KH. Ahmad Dahlan was a prominent Indonesian figure who had ideas about renewing Islamic education and became a milestone in Indonesia's revival of Islamic education. This research aims to discover how institutional innovation in Islamic education, according to KH. Ahmad Dahlan, and its relevance in the modern era. This research uses a qualitative approach with a library study type of research. This research shows that KH. Ahmad Dahlan founded many educational institutions that integrated religious and general knowledge. He also implemented a modern education management system from Western schools guided by Islamic teachings. KH. Ahmad Dahlan's thoughts on education are relevant in modern life. KH. Ahmad Dahlan's thoughts on the education system have significantly contributed to the quality of education in Indonesia and its relevance in a global context.